What university utopia does the 21st century dream of? (2021)
The present text just intends to take a glance of the daily life of an ancient social institution, that is a witness of many historical facts such as the change from feudalism to capitalism, the renaissance, the illustration, the industrial, social and d techno-cientific revolution of present time: the university. After a fast review of its history since it began in the XII and XIII centuries, the text continues with a shallow description of its current state, to finally present some reflections about its possible and desirable future. The article focuses, fundamentally, in the representative degree that the university has had in the socio-cultural contexts of each historical moment, through its basic functions of teaching, investigation and extension. In fact starting from its compromise of being the critical conscience of the society, the degree of pertinence of the university is shown in relation to the processes of social, tecnoscientifical and human development.